2017
DOI: 10.3233/jbr-160146
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of bioactive compounds in fruits and leaves of strawberry cultivars

Abstract: BACKGROUND: Strawberries (Fragaria × ananassa Duch.), the most popular berries grown and consumed all over the world, have a unique composition of bioactive compounds, including polyphenols that determine the quality, nutritional value and sensorial properties of those fruits. The study has provided data suggesting that there are links between the presence of bioactive compounds in strawberry leaves and the presence of those compounds in strawberry fruit. OBJECTIVE: Newly released and standard June-bearing str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
(71 reference statements)
0
20
0
1
Order By: Relevance
“…The higher content of glucogallin in proportion with tri-and tetra-galloyl glucose across all N treatments in both cultivars could indicate reduced kinetics of the galloyltransferases compared to glucosyltransferase in the applied N treatment. Across plant species, it has been reported that GT and ET are not simultaneously produced (Salminen and Maarit, 2011) and that strawberry leaves have a higher abundance of ET compared to polymeric GTs (Kim et al, 2016;Kårlund et al, 2016;Michalska et al, 2017). The preferential biosynthesis of ET in strawberry leaves over GT could be due to preferential oxidation of the branch point substrate pentagalloylglucose, as opposed to the formation of a depside bond between the gallic acid subunits.…”
Section: Variation In the Composition Of Phenolic Classes In Response To Varied Nitrogen Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The higher content of glucogallin in proportion with tri-and tetra-galloyl glucose across all N treatments in both cultivars could indicate reduced kinetics of the galloyltransferases compared to glucosyltransferase in the applied N treatment. Across plant species, it has been reported that GT and ET are not simultaneously produced (Salminen and Maarit, 2011) and that strawberry leaves have a higher abundance of ET compared to polymeric GTs (Kim et al, 2016;Kårlund et al, 2016;Michalska et al, 2017). The preferential biosynthesis of ET in strawberry leaves over GT could be due to preferential oxidation of the branch point substrate pentagalloylglucose, as opposed to the formation of a depside bond between the gallic acid subunits.…”
Section: Variation In the Composition Of Phenolic Classes In Response To Varied Nitrogen Supplymentioning
confidence: 99%
“…In the present study, the decrease in the kaempferol:quercetin ratio with decreases in the N treatment was attributed to an increase in quercetin and not to a decrease in kaempferol. Regardless of the stress factor, quercetin is reported as a more abundant flavonol in strawberry fruits and leaves compared to kaempferol (Kårlund et al, 2016;Michalska et al, 2017). The dihydroxylated flavonol quercetin has higher superoxide radical scavenging activity than the monohydroxylated kaempferol (Marković et al, 2014;Zhang et al, 2015).…”
Section: Variation In the Composition Of Phenolic Classes In Response To Varied Nitrogen Supplymentioning
confidence: 99%
“…The presence of these components determines the quality, nutritional value, and sensorial properties of fruits. The activity of enzymes involved in their biosynthesis is influenced by many environmental factors, particularly by light intensity and light spectrum (red, blue, UVB) [19,56]. Moreover, the biosynthesis of different phenolic compounds depends on the plant genotype and cultivation conditions [57].…”
Section: Biochemical Analysis Of Leaves and Fruitsmentioning
confidence: 99%
“…Fruits may vary in terms of the composition of polyphenols depending on the cultivar, growing conditions, and ripeness stage. The dominant group of polyphenols in (wild) strawberry fruit are anthocyanins with pelargonidin-3-glucoside being the major one [19].…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry is one of the most widespread berry crops in the world. Its popularity is due to such traits as early harvest maturity, dessert taste, aroma and rich biochemical composition of the fruit [1,2]. It should be noted that the strawberry breeding is mainly aimed at improving the commercial qualities of fruits, productivity and plant resistance to unfavorable biotic factors, while the improvement of such consumer qualities as the biochemical composition and aroma of fruits was carried out insufficiently, which led to a decrease in these traits in many widely cultivated strawberry varieties [3,4].…”
Section: Introductionmentioning
confidence: 99%